Taxonomical Study of The Genus Oxalis L. (Oxalidaceae) in Iraq - Al-Hussaini, Aseel F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The current study included collection for many fresh specimens, the observation of specimens in some Iraqi herbaria have been studied, although morphological characters of roots, stems, flowers, inflorescences and fruits were included in this work, however indumentums  and pollen grains were studied